PENGARUH GAYA KEPEMIMPINAN KEPALA SEKOLAH, KOMITMEN GURU, MOTIVASI GURU TERHADAP KINERJA GURU YAYASAN PPAY AL AMAL DI KOTA SURABAYA - jurnalpps pps; Siti Nur Afiyati (Prodi Magister Manajemen Universitas Wijaya Putra, 2021)
The purpose of this study was to describe and analyze the effect of both partially and simultaneously the principal's leadership style, teacher commitment, and teacher motivation, which had a dominant effect on teacher performance. The population in this study were all SD, SMP, and SMK teachers in the PPAY AlAmal Foundation environment in Surabaya with totaling 67 people. This type of research is explanatory with a quantitative approach. The results showed that the principal's leadership style, teacher commitment, teacher motivation, partially or simultaneously had a significant effect on teacher performance. Of the three independent variables, the teacher commitment variable has a dominant influence on teacher performance. Keywords: leadership style, commitment, motivation, performance